2020
DOI: 10.1007/s00213-020-05622-9
|View full text |Cite
|
Sign up to set email alerts
|

The infralimbic cortex and mGlu5 mediate the effects of chronic intermittent ethanol exposure on fear learning and memory

Abstract: Rationale and Objectives-Alcohol use disorder (AUD) and post-traumatic stress disorder (PTSD) often occur comorbidly. While the incidence of these disorders is increasing, there is little investigation into the interacting neural mechanisms between these disorders. These studies aim to identify cognitive deficits that occur as a consequence of fear and ethanol exposure, implement a novel pharmaceutical intervention, and determine relevant underlying neurocircuitry. Additionally, due to clinical sex differences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 119 publications
1
7
0
Order By: Relevance
“…We observed that male Air control rats displayed both within-session and between-session reductions in the percentage of time spent freezing in response to CS presentation. This observation is consistent with previous studies that also utilized a protracted extinction protocol ( Elias et al, 2010 ; Smiley et al, 2020 ; Smiley et al, 2021a ). While some within session differences in freezing between the Air control and AIE exposed rats were noted, there was no significant difference in extinction of conditioned freezing when examined across days of extinction training.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…We observed that male Air control rats displayed both within-session and between-session reductions in the percentage of time spent freezing in response to CS presentation. This observation is consistent with previous studies that also utilized a protracted extinction protocol ( Elias et al, 2010 ; Smiley et al, 2020 ; Smiley et al, 2021a ). While some within session differences in freezing between the Air control and AIE exposed rats were noted, there was no significant difference in extinction of conditioned freezing when examined across days of extinction training.…”
Section: Discussionsupporting
confidence: 93%
“…Rats were tested using a fear conditioning, extinction and recovery paradigm that is based on previously published studies ( Smiley et al, 2020 ; Smiley et al, 2021b ). As is depicted in Figure 1B , an “ABBAB” contextual design was used to assess conditioned fear acquisition, cued fear extinction, extinction recall (retention), context-dependent fear renewal, and spontaneous recovery ( Cain et al, 2012 ; Vanelzakker et al, 2013 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Stephens shows reduction in fear acquisition for binge drinkers but sees generalization of fear in them. However, fear extinction has been shown to consistently become weaker after chronic alcohol exposure (26,27,30). In this paper, we aim to reproduce the impaired fear extinction by incorporating known alterations produced by alcohol in the amygdala circuitry in a computational model.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, microdialysis analysis showed that alcohol modulates the release of glutamate by parvalbumin-expressing interneurons in the rat medial prefrontal cortex (mPFC) [6]. Other rat studies showed that the glutamatergic signaling in the infralimbic subregion of the PFC facilitated extinction of alcohol-seeking behaviors [7], while activity-dependent ablation of neurons in parts of the PFC induced excessive alcohol seeking in rats [8]. In addition, pharmacological blockade of glutamate receptors in the basolateral amygdala and nucleus accumbens reduced cue-induced reinstatement of alcohol in rats [9].…”
Section: Introductionmentioning
confidence: 99%